A Bemisia tabaci midgut protein interacts with begomoviruses and plays a role in virus transmission. (17th November 2015) - Rana, Vipin Singh; Popli, Sonam; Saurav, Gunjan Kumar; Raina, Harpreet Singh; Chaubey, Rahul; Ramamurthy, V. V.; Rajagopal, R.
Summary: Begomoviruses are a major group of plant viruses, transmitted exclusively by Bemisia tabaci (Gennadius) in a persistent circulative non‐propagative manner. The information regarding molecular and cellular basis underlying Begomovirus – whitefly interaction is very scarce. Evidences have suggested that the insect gut possesses some crucial protein receptors that allow specific entry of virus into the insect haemolymph. We have performed yeast two hybrid gut cDNA expression library screening against coat protein of Tomato leaf curl New Delhi virus (ToLCV) and Cotton leaf curl Rajasthan virus (CLCuV) as bait. Midgut protein (MGP) was the common protein found interacting with both ToLCV and CLCuV. MGP was localized in whole mount B . tabaci as well as in dissected guts through confocal microscopy. Pull down and dot blot assays confirmed in vitro interaction between ToLCV/CLCuV coat protein and MGP. Immunolocalization analysis also showed colocalization of ToLCV/CLCuV particles and MGP within insect's gut. Finally, anti‐MGP antibody fed B . tabaci, exhibited 70% reduction in ToLCV transmission, suggesting a supportive role for MGP in virus transmission.